Geographic variation in Epstein-Barr virus-associated Burkitt's lymphoma in children from Brazil - Klumb, C. E.; Hassan, R.; Oliveira, Deilson Elgui de [UNESP]; De Resende, LMM; Carrico, M. K.; Dobbin, J. D.; Pombo-de-Oliveira, M. S.; Bacchi, C. E.; Maia, R. C. (Wiley-Blackwell, 2004)
In developing countries, BL has a strong association with EBV infection during childhood. In South America, the data have shown an EBV association intermediate between that reported in the United States (30%) and that in equatorial Africa (95%). Early age at EBV infection and lower socioeconomic status have been related to increased EBV-associated BL in developing countries. In Brazil, there are not enough data on childhood BL related to EBV infection. Our aim was to evaluate the clinicopathologic features and EBV association of 44 children with NHL from the state of Rio de Janeiro, situated in the southeast of Brazil. EBV was detected using RNA in situ hybridization in 36 biopsy specimens. DNA from fresh tumor samples and from paraffin-embedded tissues of patients were analyzed by PCR, in which the first reaction included primers for an EBNA-2 common region while the nested reaction amplified the region discriminating between EBV types I and 2 in separate reactions. EBV was detected in 21 of 29 BLs (72%), and type I virus infected the majority of EBV-positive BLs (18/21). There was a trend for younger age in children with EBV-positive BL compared to EBV-negative BL (median age 4 compared to 6 years, respectively; p = 0.056). Our study confirmed that in the southeast of Brazil BL had an intermediate association with EBV. A higher rate of EBV-associated BL was described in the northeast of Brazil. These differences are probably related to regional socioeconomic status. In conclusion, our study suggests that early infection with EBV in the background of a low socioeconomic condition associated with other environmental factors could contribute to BL in Brazil. (C) 2003 Wiley-Liss, Inc.
Keywords: Burkitt's lymphoma; Epstein-Barr virus; Brazil; childhood non-Hodgkin's lymphoma